METHOD OF DEVELOPMENT PLAYING MICRO ROLES USING PUPPETS TO IMPROVE THE EMOTIONAL SOCIALIZATION OF CHILDREN AGED 5-6 YEARS OLD AT LENDANG BEDURIK SEKARTEJA VILLAGE 2020 - Ainunnisa’ul Husna; Baik Nilawati Astini; Fahruddin Fahruddin; I Made Suwasa Astawa (Indonesian Publication Center, 2020)
The purpose of this research is to develop a micro role playing method using puppets that can improve the social emotional of children aged 5-6 years in the Lendang Bedurik neighborhood of Sekarteja Village in 2020. This type of research is development research with reference to the opinion of Borg & Gall. The research subjects were children aged 5-6 years in Lendang Bedurik, Sekarteja Village. Methods of data collection in this study using the method of observation, documentation, and FGD (Focus Group Discussion). The data analysis technique in this research was descriptive qualitative. The research used three stages of development with six meetings. Each stage an increase occurs by modifying the tools and materials, the steps of the game, and the rules of the game. The results obtained at the development stage I (meeting I) obtained a percentage value of (41.45%). there was an increase in stage I (meeting II) by (46%), at development stage II (meeting III) it increased again to reach (50.16%), at development stage II (meeting IV) of (69.8%), in development stage III (meeting V) was (81.68%), development stage III (meeting VI or last) was (86.06%).